Lemierre Syndrome in a Patient With Splenectomy Secondary to Pyruvate Kinase Deficiency, Complicated by Heparin Resistance. (August 2021) - Clark, Kiley; Sly, Morgan; Chan, Pearl; Lai, Hobart; Ali, Hadi; Contreras, David; Sidhu, Ramanjeet; Bhandohal, Janpreet; Mishra, Sikha; Kuran, Rasha; Polineni, Rahul Dev
Lemierre syndrome was first documented in the literature in 1936, and is defined as septic thrombophlebitis of the internal jugular vein. It is typically a result of oropharyngeal infection causing local soft tissue inflammation, which spreads to vasculature, and promotes formation of septic thrombi within the lumen, persistent bacteremia, and septic emboli. We present the case of a 24-year-old incarcerated man, who presented with leukocytosis and a right-sided tender, swollen neck after undergoing left mandibular molar extraction for an infected tooth. Computed tomography revealed a persistent thrombus in the transverse and sigmoid sinuses bilaterally, extending downwards, into the upper jugular veins. He was started on empiric intravenous vancomycin, zosyn, and heparin, but subsequently demonstrated heparin resistance, and was thus anticoagulated with a lovenox bridge to warfarin. Throughout his hospital course, hemocultures demonstrated no growth, so antibiotic treatment was deescalated to oral metronidazole and ceftriaxone. On discharge, the patient was transitioned to oral amoxicillin and metronidazole for an additional 4 weeks with continuation of anticoagulation with warfarin for a total of 3 to 6 months. This case report details a unique presentation of Lemierre syndrome with bilateral transverse sinus, sigmoid sinus, and internal jugular vein thrombosis that was presumably secondary to an odontogenic infectious focus.